How people with diabetes evaluate participation of their family in their health care - Aliny de Lima Santos; Sonia Silva Marcon (Universidad de Antioquia, 2014)
Objective. To understand how individuals with diabetes evaluate the participation of their family in their health care. Methodology. This was a descriptive study with a qualitative approach involving 26 individuals in the Diabetes Association of Maringá. Participating in the study were 9 women and 17 men (age range, 38 to 83 years) who had attended at least one educational meeting of the "culture circles" of the association. We used the methodological reference of Paulo Freire for implementing an educational proposal directed at persons with type 2 diabetes mellitus that overcame the limitations of conventional health education approaches. Data were collected between May and July 2011. Testimonials given in meetings were recorded, transcribed, and analyzed according to thematic structures. Results. Three thematic structures appeared: 1) Recognizing the importance of family in the care of patients with diabetes, 2) blaming the family for non-adherence to healthy practices, and 3) perceiving a secondary gain of the disease: feeling cared for by family members. Conclusion. Patients with diabetes perceive family as a source of support and stimulus for adherence and healthy practice, which enable them to control the disease. Family participation in a patient's care plan should be encouraged.